2006
DOI: 10.1186/1471-2261-6-38
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, vitamin B12 and folate levels in premature coronary artery disease

Abstract: Background: Hyperhomocysteinemia is known as an independent risk factor of atherosclerosis, but the probable role of hyperhomocysteinemia in premature Coronary Artery Disease (CAD) is not well studied. The aim of this study was to assess the role of hyperhomocysteinemia, folate and Vitamin B12 deficiency in the development of premature CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 36 publications
3
60
1
6
Order By: Relevance
“…Furthermore, plasma Hcy levels were associated with arterial stiffness only in males [35]. Circulating Hcy levels were also significantly higher in males with CHD than in males without CHD, whereas no difference was observed in Hcy levels in females with regard to CHD [36]. As for lipid profiles, TG and HDL-C seem to be better predictors of CHD risk than TC or LDL-C in females [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, plasma Hcy levels were associated with arterial stiffness only in males [35]. Circulating Hcy levels were also significantly higher in males with CHD than in males without CHD, whereas no difference was observed in Hcy levels in females with regard to CHD [36]. As for lipid profiles, TG and HDL-C seem to be better predictors of CHD risk than TC or LDL-C in females [15].…”
Section: Discussionmentioning
confidence: 99%
“…Kawashiri et al 13 reported that plasma homocysteine level of subjects in younger IHD group was significantly higher than that of subjects in older IHD group. Sadeghian et al 14 concluded that hyperhomocysteinemia is an independent risk factor for CAD in young especially in men.…”
Section: Discussionmentioning
confidence: 99%
“…Vários defeitos genéticos estão associados, entre eles, o acúmulo de homocisteína (Hcy) no sangue (9,14,19) . A concentração plasmática de homocisteína é influenciada tanto por fatores nutricionais, como concentração do ácido fólico e vitaminas B6 e B12, quanto por fatores hereditários, especialmente os ligados às enzimas do metabolismo da metionina e da cisteína (1) .…”
Section: Frequência Genotípica Em Amostras De Mthfr Para O Polimorfisunclassified